The Role of Cytokines in Activation of Coagulation and Fibrinolysis in Dengue Shock Syndrome - Suharti, Catharina; van Gorp, Eric C.M.; Setiati, Tatty E.; Dolmans, Wil M.V.; Djokomoeljanto, Robert J.; Hack, C. Erik; ten Cate, Hugo; van der Meer, Jos W.M. (Thrombosis and Haemostasis, 2002)
In a prospective clinical study of 50 patients with Dengue Shock Syndrome (DSS), we investigated the association of tumor necrosis factor-a (TNF-a), interleukin-1f3 (IL-1f3), IL-1 receptor antagonist (IL-1Ra), and IL-6 with activation markers of coagulation (F1+2 and TATc) and fibrinolysis (t-PA, PAPc, and D-dimer). We found that TNF-a, IL-1f3 and Il-1Ra, but not IL-6, concentrations were elevated in the circulation during the early stage of infection and at discharge from hospital. TNF-a was significantly associated with D-dimer, an activation marker of fibrinolysis (p < 0.003), but not with activation markers of coagulation. IL-1f3 was significantly associated with t-PA (p < 0.03). IL-1Ra was significantly associated with F1+2, TATc (p < 0.04 and p < 0.02, respectively), whereas IL-6 was significantly associated with both, activation markers of coagulation (F1+2; p < 0.03) and fibrinolysis (PAPc; p = 0.002). Our data are in line with studies in bacterial sepsis. In severe dengue virus infection the same cytokines are involved in the onset and regulation of hemostasis.
Keywords: Cytokines; coagulation; fibrinolysis; dengue shock syndrome